Learning From Love Island? Diversification of the Hegemonic Man - Nichols, Kitty (Frontiers in Sociology, 2019)
It is undeniable that Love Island promotes specific ideas of masculinity and masculine behaviours. There is an ‘expected’ masculinity performed in the villa, exemplified in cases such as ‘The Do Bits Society’ which advocates heteronormative forms of masculinity and gender relations (Whitehead and Barrett, 2008). Within such examples men had to successfully perform what Schrock and Schwalbe (2009) refer to as ‘manhood acts’ in order to prove their masculine identity. This form of masculinity, which dominated the space, can be explained sociologically via intersecting hegemonic and performance theorising (Goffman, 1974; Connell, 2005; Butler, 2008; Wellard, 2009). However, utilising new combinations of theoretical approaches, this paper will explore more diverse performances of masculinity which were present in the villa. This includes the ways that men were making choices in the construction of their masculine identities beyond the ‘expected’ form which dominated, as well as how women also performed this form of masculinity. Through these discussions, this paper will challenge understandings of gender and gendered relationships, using Love Island as a catalyst to argue that the boundaries of gender theory are changing.